Electrochemical and Spectroscopic Studies on the Interaction between (1,10-Phenanthroline- N,N’)-nickel(II) phthalate and DNA - Zhang, Shu-Sheng; Niu, Shu-Yan; Wang, Long; Wan, Jun; Li, Xue-Mei (Asian Journal of Chemistry, 2010)
The crystal structure of ([Ni(phen)](phth)(H2O).H2O (1) [Ni(phen)]2+) (phen = 1,10-phenanthroline, phth = phthalate) was determined by X-ray crystallography. The interaction between [Ni(phen)]2+ and salmon sperm DNA in 0.2 mol L-1 Britton Robinson buffer solution (pH 6.50) was studied by cyclic voltammetry, ultraviolet spectroscopy and fluorescence spectroscopy. All the experimental results indicate that [Ni(phen)]2+ can bind to DNA mainly by intercalative binding mode. The binding ratio of the DNA-[Ni(phen)]2+ association complex is calculated to be 1 : 1 and the binding constant is 8.28 x 102 L mol-1.